PELATIHAN PEMBUATAN AMONIASI JERAMI PADI BAGI KELOMPOK PETERNAK DI DISTRIK PRAFI KABUPATEN MANOKWARI - B. Santoso; B.T. Hariadi; D. Sawen (Buletin Udayana Mengabdi, 2016)
The aim of community service was to introduce the technique of making ammoniated rice straw for farmermembers of Harapan Makmur and Tani Ternak Terpadu Sebelas groups. The activity was conducted during8 months (March to October 2015) at Prafi Districk, Manokwari Regency. The activities of communityservice consisted of introduce the technique of making ammoniated rice straw, demonstration and practice ofmaking ammoniated rice straw. Materials of ammoniated rice straw comprised rice straw, urea and water.The mixture of that materials was stored in polybag for 35 days. Farmer of both groups were very interestedin the topic of making ammoniated rice straw. The process rice straw by applying urea (ammoniation)increased crude protein content by 86.7% dan decreased crude fiber by 10.1%.